Spatial variability of soil nutrients under sugarcane cropping system in semi-arid tropics of western India using geostatistics and GIS - DONGARE, VISHAKHA T.; REDDY, G.P. OBI; KHARCHE, V.K.; RAMTEKE, I.K. (Journal of Soil and Water Conservation, 2022)
The present study aimed to assess the spatial variability and mapping of soil macro and micro nutrients under sugarcane cropping system in semi-arid tropics of western Maharashtra using geostatistics and Geographic Information System (GIS). Totally 205 surface soil samples were collected at 200 x 200 m interval using the grid sampling technique in three distinct landforms. In order to assessand mapping the spatial variability of soil fertility properties, geo-statistical analysis was carried out by using best fitted models in GIS. The geostatistical analysis shows that Standardized Root Mean Square Error (RMSSE) for almost all variables expect for CaCO3 (0.96) and Mn (0.97) were close to one, which indicates a good prediction. Results showed that the available N and P varied from 125.4 to 216.4 and 7.2 to 19.7 kg ha-1, respectively, whereas, available K was ranged from 278.7 to 975.2 kg ha-1. The available Mn and Cu status of soils were sufficient with 4.12 to 21.12 and 1.57 to 4.68 mg kg-1, respectively. However, significant portion of the study area showed deficiency of available Zn. The assessed spatial variability of various soil nutrients helps in site-specific nutrient management and crop planning decisions to improve sugarcane productivity.